Child caregiver's concepts on child development - Enriquez, Catherine Ulrica Pobre (Animo Repository, 2011)
This study focused on the child caregivers concepts on child development particularly on cognitive and language, socio-emotional and physical domains. This research utilized descriptive method and content analysis of the qualitative approach. Interviews and observations were conducted to gather data. Purposive sampling and referral sampling were used to obtain the twelve (12) participants. Results revealed that the despite the fact that most child caregivers have less or no formal schooling, their knowledge and understanding of the concepts on child development which includes the learning strategies and child development principles show that they have awareness and understanding how children grow, learn and develop. Seminars and trainings will be of great help for the child caregivers to be more equipped with knowledge and skills on child development, thus, providing quality child care. Another finding is that most of the child caregivers use their experiences in taking care of the child or children under their care. Lastly, child caregiver respondents see their role as nurturers, teachers, and guide the childrens behavior. The results and findings from this study could be used in the development of a framework and program for the child caregiver seminars and workshops provided by some schools and organizations. In the same manner, it is recommended that parents to a background check on the child caregivers and the tool used in this study will be of help in identifying the child caregivers knowledge and understanding of the concepts on child development.